2018
DOI: 10.1002/jtr.2250
|View full text |Cite
|
Sign up to set email alerts
|

Ownership structure and firm performance of listed tourism firms

Abstract: Ownership structure has been identified as a critical governance component due to its effect on firm performance. Within ownership structure, issues of institutional shareholders, cash flow rights of controlling owners, and ownership discrepancy have not been examined in the tourism sector. The current study uses listed tourism firms in Taiwan to empirically examine how these three variables influence firm performance.Results show a positive effect on return on assets and Tobin's Q from the presence of institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 165 publications
7
40
0
6
Order By: Relevance
“…institutional or sponsor/director shareholders) attempt to control the actions of both managers and other classes of shareholders. This is supported by several prior studies which documented that the agency problem may shift from owner to manager to owner to owner (between controlling owner and minority or non-controlling owner) when a particular group of owner attempted to control the operation and management of the companies (Shleifer and Vishny, 1997;Yeh, 2019). Prior literature also documented that board characteristics and ownership structures are the most crucial firm-specific determinants of good governance of a company (Khanchel, 2007).…”
Section: Ownership Structure and Firm Performancementioning
confidence: 71%
See 2 more Smart Citations
“…institutional or sponsor/director shareholders) attempt to control the actions of both managers and other classes of shareholders. This is supported by several prior studies which documented that the agency problem may shift from owner to manager to owner to owner (between controlling owner and minority or non-controlling owner) when a particular group of owner attempted to control the operation and management of the companies (Shleifer and Vishny, 1997;Yeh, 2019). Prior literature also documented that board characteristics and ownership structures are the most crucial firm-specific determinants of good governance of a company (Khanchel, 2007).…”
Section: Ownership Structure and Firm Performancementioning
confidence: 71%
“…However, the findings of these studies are rather inconclusive and misleading (Tam and Tan, 2007). Though majority of the prior studies demonstrated positive association between institutional ownership (Omran et al, 2008;Kansil and Singh, 2018;Yeh, 2019), foreign ownership (Ferreira and Matos, 2008;Bentivogli and Mirenda, 2017;Kao et al, 2018) and director ownership (Kao et al, 2018;Hanafi et al, 2018) and firm performance, others documented negative (Muttakin et al, 2012) or no association (Demsetz and Villalonga, 2001). The underlying reason for such findings may be attributed to the fact that owners/shareholders have limited capacity, in majority of the cases, to influence the activities of management (as general shareholders cannot take part in the day to day operation or crucial decision making process) unless they take part in the corporate board.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Meski begitu peran pemilik saham memiliki batasan di mana mereka tidak bisa terlibat langsung dalam keputusan-keputusan penting yang bersifat teknis (Rashid, 2020). Semakin besar kepemilikan saham, maka semakin besar pula hak dalam pengendalian perusahaan dan yang dimaksud pengendalian disini adalah seberapa besar kemampuan pemilik saham dalam memengaruhi operasi perusahaan dan manajemen (Yeh, 2019). Fungsi pengendalian tersebut dapat langsung memengaruhi tindakan manajer yang tidak sesuai dengan harapan pemilik saham, agar manajer bertindak dalam rangka memenuhi ekspektasi dari pemilik saham.…”
Section: Kata Kunci: Struktur Kepemilikan Kinerja Perusahaan Karakteristik Dewan Komisaris Pendahuluanunclassified
“…The external control system are the market policies, product and services image, market competitors and investors control (Jensen, 1986; La Porta, Lopez‐de‐Silanes, Shleifer, & Vishny, 1997). The literature is available in many ways like as determining the interlinkage with of ownership characteristics, board composition and firm performance (Abdallah & Ismail, 2017; Arosa, Iturralde, & Maseda, 2010; Bauwhede, 2009; Belkhir, 2009; Bhagat & Bolton, 2008; Chiang & Lin, 2007; Górriz & Fumás, 1996; Kapopoulos & Lazaretou, 2007; Lam & Lee, 2012; Lefort & Urzúa, 2008; Love & Klapper, 2002; Maury, 2006; Nicholson & Kiel, 2007; Phung & Mishra, 2016; Singh & Gaur, 2009; Tam & Tan, 2007; Yeh, 2019). In the Pakistan context, different studies are available such as (Afgan, Gugler, & Kunst, 2016; Ahmed Sheikh, Wang, & Khan, 2013; Javid & Iqbal, 2008; Shah, Butt, & Saeed, 2011; Yasser & Mamun, 2015; Yasser, Mamun, & Rodrigs, 2017).…”
Section: Introductionmentioning
confidence: 99%